PENGARUH EXPERIENTIAL MARKETING, CITRA PERUSAHAAN DAN KEPUASAN TERHADAP LOYALITAS PELANGGAN RESTORAN SEDERHANA MASAKAN PADANG DI PANDANARAN SEMARANG (Students' Journal of Economic and Management, 2015)
This study takes an object in a simple restaurant cuisine Pandanaran Meadow in Semarang. The reason for choosing the object of the study is based for the visitors who come here every week to change up and down, and can be indicated that the customers who come here have not been loyal. Of the phenomenon it is necessary to evidence and research of analyze the influence of experiential marketing, corporate image and satisfaction on customer loyalty. The sample was taken of 100 respondents, the sample collection method is purposive sampling is the selection of samples from a population based on the criteria specified. Methods of data analysis using linear regression and methods of data collection using the questionnaire. The test results showed that (1) experiential marketing to the satisfaction showed a positive and significant influence, (2) the image of the company on customer loyalty showed a positive and significant influence, (3) satisfaction on customer loyalty showed a positive and significant influence. Keywords: experiential marketing, corporate image, customer satisfaction and loyalty